Lifestyle and demographic factors associated with human semen quality and sperm function. (3rd September 2018) - Shi, Xiao; Chan, Carol Pui Shan; Waters, Tarah; Chi, Ling; Chan, David Yiu Leung; Li, Tin-Chiu
ABSTRACT: In this study, we sought to investigate the effect of lifestyle and demographic factors on classic and functional semen parameters. Three hundred and twenty-eight subjects who underwent semen analysis were recruited. Routine SA, sperm vitality, acrosome reaction (AR) assay and sperm DNA fragmentation index (DFI) were analyzed. Demographic and lifestyle information, including (1) BMI, (2) current smoking and alcohol drinking frequency, (3) sleep habits, (4) daily fluid intake, (5) weekly meat intake, (6) sports frequency, (7) trouser cell phone use, (8) age, and (9) abstinence time, were collected. Generalized additive models were used to analyze the possible non-linear association. The results showed that total sperm count (TSC) was significantly associated with age ( P = 0.001), abstinence time ( P = 0.001) and daily coffee intake ( P = 0.044). Semen volume was significantly associated with age ( P < 0.001) and daily coffee intake ( P < 0.001). Sperm concentration was significantly associated with abstinence time ( P = 0.011) and average sleep duration ( P = 0.010). Sperm motility was significantly associated with age ( P = 0.002) and daily juice intake ( P = 0.001). Total motile sperm count was significantly associated with age ( P = 0.003) and abstinence time ( P = 0.009). DFI was significantly associated with age ( P = 0.002), irregular sleeping habit ( P = 0.008) and abstinence time ( P = 0.032). The percentage of AR sperm was significantly associated with daily juice intake ( P = 0.013). In conclusion, DFI and TSC were the most sensitive semen parameters for demographic and lifestyle features, whereas age had more influence on semen parameters than other demographic and lifestyle features. Abbreviations : BMI: body mass index; SA: semen analysis; AR: acrosome reaction; DFI: DNA fragmentation index; GAM: generalized additive model; TSC: total sperm count; TMC: total motile sperm count; IUI: intrauterine insemination; SCSA: sperm chromatin structure assay; SD: standard deviation; IQR: interquartile range; CBAVD: congenital bilateral absence of vas deferens; NEQAS: national external quality assessment service; HTF: human tubal fluid; HSA: human serum albumin.